Case Report: transjugular intrahepatic portosystemic shunt combined with hemodialysis for refractory ascites treatment in a patient with idiopathic non-cirrhotic portal hypertension and uremia - Li, Ying; Quan, Xin; Wu, Hao (Frontiers in Medicine, 2025)
Transjugular intrahepatic portosystemic shunt is a standard treatment for refractory ascites (RA) in patients with cirrhosis. Idiopathic non-cirrhotic portal hypertension (INPH) is a disorder of unknown etiology, clinically characterized by features of portal hypertension. The current therapy is limited to managing portal hypertension and is recommended to be referred to as cirrhosis. Given the elevated risk of overt hepatic encephalopathy (OHE) post-TIPS, TIPS placement is limited in cirrhotic patients with concurrent acute or chronic kidney disease. However, patients with INPH exhibit better liver function and ammonia metabolism than those with liver cirrhosis. The efficacy of TIPS for RA in INCPH patients with uremia on dialysis remains uncertain. We present a case of TIPS placement for RA in a patient with INPH on maintenance hemodialysis for uremia, aiming to explore therapeutic advancements and enhance quality of life in this challenging population.